Clinical Epidemiology of the Global Expansion of Klebsiella Pneumonia - Ali, Saja Sattar Jaber; Juma, Moeaml Wahed motar; Mohammed, Abdulkareem Abdullah Maakit; Dhiyab, Ridha Majhool Atya (American Journal of Biomedicine and Pharmacy, 2024)
Klebsiella pneumoniae BSIs are associated with high mortality rates worldwide. The emergence of antibiotic-resistant K. pneumoniae complicates the management of infections caused by these bacteria. This study aimed to evaluate the epidemiology, resistance profiles, and clinical outcomes of K. pneumoniae BSIs. The infection rate was slightly higher in females (52%) than in males (48%). The ICU and ER had the highest prevalence of K. pneumoniae BSI. ICUs are considered factories that create, amplify, and disseminate antibiotic resistance [20, 21]. The high prevalence of antibiotic resistance in ICUs might be due to multiple infections, frequent application of antimicrobials, or the frequent use of invasive procedures. In our study, Klebsiella pneumoniae BSIs in patients admitted to the ICU were significantly associated with multiple risk factors including carbapenem resistance, mechanical ventilation, respiratory infection, multi-organ dysfunction, ischemic heart disease, and septic shock were significantly higher among ICU patients than non-ICU patients. In a recent study by Wang et al. (2023), age over 70 years, admission to ICU, and urinary tract infection were found to be the risk factors for Carbapenem-resistant and ESBL-KP-resistance.